From Preschool to Prosperity The Economic Payoff to Early Childhood Education - Bartik, Timothy J. (W.E. Upjohn Institute, 2014)
Bartik shows that investment in high-quality early childhood education has several long-term benefits, including higher adult earnings for program participants.